Problems in Adolescents, Mindfulness and School Performance in High School Students. Preliminary Study - Mercader Rovira, Alberto (2020)
This paper discusses the importance of emotional education to reduce adolescent problems and emphasizes emotional competence and self-regulation as basic elements of competency education in the school context, based on research in recent decades, especially linked to the role of Executive Functions. In addition, some results of programs and therapies with Mindfulness or conscious attention to the present moment in children and adolescents are presented and the little presence of research is observed, even in Peru. The results of an ex post facto study are presented with a sample (N = 76) of IE High School students Jorge Basadre Grohmann from Trujillo, Peru, where is described the problems in adolescents and compared them with the capacity for conscious attention and academic performance. We noted that the students presented clinical significance in problems of self-esteem (25.4%) and depression (11.8%) and that there was few relationship between the ability to be aware at the present moment with anxiety (ρ= -,349, p,005), depression (ρ= -473, p,000), interpersonal problems (ρ= -,309, p,014), uncertainty about the future (ρ= ,421, p,001) and psychosocial risk (ρ= -,409, p,001). No significant relationships were detected between adolescent problems and academic grades, although associations between grades were observed. The article aims to makeanothercontribution for the study of the emotional problems in Peruvian adolescents and to promote the development of education policies based on emotions, a theme in whichthereisstill along way to go.